(untitled) (Journal of Universal Science Research, 2023)
The article provides examples of the construction of medical eponyms in English and problems in translating them into Russian. Eponyms as part of the language of science contribute to a deeper understanding of human activity and its culture. The sublanguage of medicine is the most important source of knowledge about the people who created this science, and the current trend in modern linguistics towards the study of the human factor allows us to consider eponymous terms in the light of a cognitive approach.